A study on wear and worn surfaces of grey cast iron affected by a novel silicate additive. (4th February 2015) - Zeng, Zhu; Tian, Bin
Abstract: A novel aluminium silicate hydroxide additive has shown excellent anti‐wear effect in practical applications and has been mainly studied on steels in laboratory conditions. In this paper, the pin‐on‐disk sliding wear tests were carried out to investigate the wear and worn surfaces of grey cast iron with additives in different concentration. It was found that the silicate additive showed an obvious anti‐wear effect and a reliable duration, reduced the number of pits and cracks on the worn surfaces and improved the nanohardness of the worn surfaces of grey cast iron disks by 72%. Furthermore, Raman spectroscopy displayed that the carbon structure of the worn surface of grey cast iron disks with the additive had an obvious transformation from nanocrystalline graphite to amorphous carbon. Copyright © 2015 John Wiley & Sons, Ltd.